EDUCATION AND HEALTH: FORGETTEN RIGHTS FOR HMONG IN BAN NONG, HADXAYFONG DISTRICT, VIENTIANE PREFECTURE, LAO PDR - Tampubolon, Manotar; Nadeak, Bernadetha; Limbong, Mesta; Rantung, Djoys Anneke; Silvanita, Ktut (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
The objective of this paper is to describe and evaluate the implementation of community service conducted by the author from the Graduate Program of Universitas Kristen Indonesia Jakarta to build community awareness of education and health, two forgotten areas that this service targeted for the Hmong tribe in Ban Nong, Hadxayfong District, Vientiane Prefecture, Laos. The steps and strategies chosen for this Hmong community outreach included a survey of health care and education opportunities and partner referrals on which the strategies were based. The strategy included counseling on healthy teeth and nails and promotion of the importance of schooling, especially for children, delivered through education, especially for young families (counseling on healthy teeth and nails and counseling on the essence of education), conducted through presentations to the participants with the support of World Prayer International. We conducted the outreach over a one-week period, during which it gave approximately 100 participants including mothers and children education and demonstrations on how to properly brush their teeth and take care of their nails to keep them free from disease. On average, 60% of the participants who attended this counseling claimed to understand how to brush their teeth properly, how to care for and clean their nails, and the importance of education for children. Awareness of the importance of maintaining healthy teeth and nails increased by 10% after they received the education. The outreach and community engagement strategy, especially the provision of toothbrush and nail clipper packs, made the outreach more effective as the researchers practiced it directly in front of the participants.